Abnormal Default Mode Network Homogeneity in Major Depressive Disorder With Gastrointestinal Symptoms at Rest - Yan, Meiqi; Chen, Jindong; Liu, Feng; Li, Huabing; Zhao, Jingping; Guo, Wenbin (Frontiers in Aging Neuroscience, 2022)
Background: Gastrointestinal (GI) symptoms are prominent in many patients with major depressive disorder (MDD). However, it still remains unclear whether MDD patients with GI symptoms have brain imaging alterations in the default mode network (DMN) regions. Methods: A total of 35 MDD patients with GI symptoms and 17 MDD patients without GI symptoms were recruited. A total of 28 healthy controls (HCs) were recruited. All participants underwent resting-state functional magnetic resonance imaging scans. Network homogeneity (NH) and support vector machine (SVM) methods were used to analyze imaging data. Results: GI symptoms group showed higher HRSD-17 total scores, factor scores than non-GI symptoms group. Compared with non-GI symptoms group and HCs, GI symptoms group showed decreased NH in the right middle temporal gyrus (MTG) and increased NH in the right precuneus (PCu). The SVM results showed that combination of NH values of the right PCu and the right MTG exhibited the highest accuracy of 88.46% (46/52) to discriminate MDD with and without GI symptoms. Conclusion: MDD with GI symptoms have more severe depressive symptoms than MDD without GI symptoms. Distinctive NH patterns in DMN exist in MDD with GI symptoms that can be applied as a potential brain imaging marker to discriminate MDD with GI symptoms from MDD without GI symptoms.